Menopause-specific quality of life of rural women - Harmeet Kaur Kang; Arshdeep Kaur; Aarti Dhiman (Wolters Kluwer Medknow Publications, 2021)
Background: Menopause is a natural process, but it causes hormonal and biological changes in the body, which can result in drastic effects on quality of life (QOL) of women. Objective: The study was conducted to assess the menopause-specific QOL (MENQOL) of rural women. Subjects and Methods: A descriptive cross-sectional design was used to assess MENQOL of rural women of the selected villages of Punjab. A total of 150 menopausal women were selected using simple random sampling technique. The MENQOL questionnaire was administered to assess the QOL in relation to menopausal symptoms. Results: The mean score of overall QOL was 3.4274 ± 0.99, which revealed a moderate impact of menopausal symptoms on the QOL. Stepwise linear regression revealed the significant impact of 16 out of 29 menopausal symptoms on QOL. Furthermore, MENQOL was found to be significantly associated with education, marital status, and sleep pattern of women. Conclusions: There is a significant effect of menopausal symptoms on QOL of women which emphasizes the need to create awareness among menopausal women regarding menopausal symptoms and management to improve their QOL.